Car Voltage and Temperature Gauge / Abd Halim Mokri and Hasrul Fazli Norhalim - Mokri, Abd Halim; Norhalim, Hasrul Fazli (2004)
Car Voltage and Temperature Gauge is a same inovation two projects by the purpose of measuring devices design to measure the temperature of the water in the radiator of car and the voltage of car battery. This project also will keep the driver learn about the condition of their car. It will show the reading of temperature and voltage by the 3 digit seven segment display. The voltage supply of this project is came from the battery of car The sensor of Car Temperature Gauge is the diode temperature that is placed in the water of car radiator. The resistance or the diode will change when the temperature of water increasing or decreasing. Meanwhile, the sensor of Car Voltage Gauge is the capacitor. It's charged up by the car's voltage. The reading of temperature of this project is in degree Celsius and the reading of voltage is m volts. However Car Voltage and Temperature Gauge will not operate simultaneously. They will separate by the switch that the driver needs to change the mode of switch to get the reading needed. The cost of this project is about RM 100.00.